PENDAMPINGAN REMAJA MELALUI PROGRAM PELAYANAN KESEHATAN PEDULI REMAJA (PKPR) DI KOTA PEKANBARU - Riski Novera Yenita; Rika Mianna; Riska Epina Hayu; Aminatul Husna (Institut Kesehatan dan Teknologi Al Insyirah, 2022)
The implementation of the Youth Care Health Service Program (PKPR) is still a lot with a minimum achievement, as is the case in Pekanbaru City, even though one of the efforts to solve problems in adolescents is through this program. The minimum achievement of the PKPR program needs attention so that the purpose of this study is to evaluate the implementation of the PKPR program in Pekanbaru City. This type of research is qualitative. The research subjects were the person in charge, the implementation officer and the selected PKPR Puskesmas extension personnel with minimum achievements. Data were collected using in-depth interviews and observation techniques. The results showed that the input component resulted in problems: The absence of human resources with special competence in handling adolescents, there was no special budget to facilitate PKPR services and most of the puskesmas had not provided service facilities according to the needs of adolescents. In the process component: Planning the puskesmas PKPR program has not been planned completely. PKPR activities have not been well organized so that the implementation of these activities is not going well, plus there is not yet full monitoring. In the output component: there are still many deficiencies in recording and reporting activities so that there is no effort to evaluate changes in future activities. In this study, the achievement of the minimum PKPR program was due to the fact that all IPUT components, processes, and outputs were not running optimally. It is better if the Pekanbaru City Health Office should further improve the quality of implementing personnel and infrastructure, the implementation of activities according to the guidelines so that they can be carried out properly.